2011
DOI: 10.1530/eje-10-0621
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cortisol responses to testing with two doses of ACTH in patients with suspected adrenal insufficiency

Abstract: Objectives: To compare the cortisol response of the 1 mg and the 250 mg ACTH test in a large study of patients with suspected adrenal insufficiency. Design: Retrospective cohort study. Methods:Single center study assessing patients tested for primary or secondary adrenal insufficiency between January 2004 and December 2007, who had both ACTH tests (1 mg and 250 mg; nZ207) within a time interval of 6 weeks. Test results were compared with a Bland-Altman plot and McNemar's test. Results: The mean difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…The advantages and disadvantages of both tests in the diagnosis of adrenal insufficiency have been extensively discussed [35,36]. Since both tests give comparable results for the serum cortisol concentration at least 30 min after stimulation and based on the fact that the "high-dose" (250 µg) corticotropin test is more comprehensively validated compared to the "low-dose" (1 µg) corticotropin test, it is suggested to perform the "low-dose" (1 µg) corticotropin test in the diagnosis of PAI only when the substance is in short supply [27,34,35,37,38].…”
Section: Diagnosis Of Primary Adrenal Insufficiencymentioning
confidence: 99%
“…The advantages and disadvantages of both tests in the diagnosis of adrenal insufficiency have been extensively discussed [35,36]. Since both tests give comparable results for the serum cortisol concentration at least 30 min after stimulation and based on the fact that the "high-dose" (250 µg) corticotropin test is more comprehensively validated compared to the "low-dose" (1 µg) corticotropin test, it is suggested to perform the "low-dose" (1 µg) corticotropin test in the diagnosis of PAI only when the substance is in short supply [27,34,35,37,38].…”
Section: Diagnosis Of Primary Adrenal Insufficiencymentioning
confidence: 99%
“…Contrasting data about SST diagnostic accuracy are reported: some authors reported a superior role of 1 μg [58,59] or 250 μg [52,54,60] SSTs, and others reported that both tests presented similar results [55,56,61].…”
Section: Standard or Low-dose Sst: That Is The Questionmentioning
confidence: 85%
“…Because the rationale for SST is the assumption that cortisol response is blunted in chronic ACTH deficiency, it is important to define when we consider the condition that probably will induce the CAI as "chronic". Few papers investigated the optimal time shift to perform SST (suggesting that it can be carried out at least 4 weeks after pituitary surgery [51,52]), but the major part of the studies proposed the stimulation test 2-3 months after surgery [53][54][55][56]. Therefore, in clinical practice, SST is scheduled 2-3 months after every HPA axis injury.…”
Section: What Is the Rationale For Sst?mentioning
confidence: 99%
See 1 more Smart Citation
“…Kazlauskaite et al 23 reviewed the literature from 1966 to 2006 and found that the low-dose corticotropin test was superior to the standard dose test. In a study by Dekkers et al ,24 in which low-dose and standard dose tests were directly compared, the investigators found that the tests produced comparable results. However, they noted that the tests can produce different results in individual patients.…”
Section: Discussionmentioning
confidence: 99%